2022
DOI: 10.1002/aenm.202202054
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electroreduction of CO2 to n‐Propanol in Two‐Step Tandem Catalytic System

Abstract: Electrocatalytic conversion of CO 2 to chemical fuels serves a two-fold purpose of energy storage and carbon offset. Among those, the efficiency of electrocatalytic reduction of CO 2 to one-carbon (C 1 ) products including CO [1][2][3] and formate [4][5][6] is approaching commercialization, while the transformation of CO 2 to C 2 products such as ethylene [7][8][9][10] and ethanol [11,12] is developing rapidly. In comparison, research on the conversion of CO 2 to high-energy C 3 fuels like n-propanol [13][14][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…18 The strategy to use CO instead CO 2 , as applied by Wang et al, 18 has led to the idea to apply a two-step cascade process in which the first step consists of converting CO 2 into CO followed by its conversion into n-propanol in a second step. Wu et al 19 showed that a tandem system consisting of two electrolyzers for converting CO 2 to CO and CO to n-propanol, resulted in a FE of 15.9% for n-propanol. Similarly, Romero Cuellar et al 20 showed that the total FE toward multi-carbon products of a one-step system using the Cu gas diffusion electrode as a working electrode was limited to 20% at a total current density of −470 mA cm −2 while the two-step configuration [using a Ag-gas diffusion electrode (GDE) as an electrode for the first step followed by Cu-GDE in the second step] led to a total FE toward C 2 and C 3 products of 62% (with about 18% of n-propanol) at a total current density of −300 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…18 The strategy to use CO instead CO 2 , as applied by Wang et al, 18 has led to the idea to apply a two-step cascade process in which the first step consists of converting CO 2 into CO followed by its conversion into n-propanol in a second step. Wu et al 19 showed that a tandem system consisting of two electrolyzers for converting CO 2 to CO and CO to n-propanol, resulted in a FE of 15.9% for n-propanol. Similarly, Romero Cuellar et al 20 showed that the total FE toward multi-carbon products of a one-step system using the Cu gas diffusion electrode as a working electrode was limited to 20% at a total current density of −470 mA cm −2 while the two-step configuration [using a Ag-gas diffusion electrode (GDE) as an electrode for the first step followed by Cu-GDE in the second step] led to a total FE toward C 2 and C 3 products of 62% (with about 18% of n-propanol) at a total current density of −300 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…86,87 To deeply exploit the potentiality of Ni-based functional porous frameworks, a series of technology combination strategies was proposed, including the photocoupled ECO 2 RR 167 and tandem catalysis of the ECO 2 RR and ECORR. 142 ) were successfully obtained with a similar 2D skeleton structure except for the Ni-O 4 and Ni-N 4 linking units (Fig. 15a and d), respectively.…”
Section: Ni-based Functional Porous Frameworkmentioning
confidence: 74%
“…9). 142 Beyond the reported tandem electrodes and one-pot tandem catalysts, precise voltage control of tandem electrolyzers enables the optimized conversion of both the ECO 2 RR to CO and ECORR towards n -propanol. Specifically, the tandem electrolyzers achieved an n -propanol FE of 15.9% together with the corresponding half-cell power conversion efficiency (CPE) of 19.3%.…”
Section: Cu-based Functional Porous Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a high percentage of C 2+ product is achieved in ECOR, most of the products are only limited to C 2 such as ethylene and acetic acid. Most importantly, high-energy-density C 3 products, such as propanol, remain difficult to obtain. Throughout the existing reports on ECOR, the selectivity of propanol is usually below 10%, which hinders further applications in industry. , Currently, the best performance of propanol electrosynthesis in ECOR is achieved by noble-metal-doped Cu-based catalysts such as Ag-doped Cu and Ag–Ru-doped Cu. , Nevertheless, considering the scarcity of precious metals and the effect of doping amount, the strict doping ratio and high cost of catalysts may limit their large-scale synthesis and use. Therefore, other cost-effective strategies for catalyst design are worth considering. C 1 –C 2 coupling is considered a crucial route for the formation of C 3 products based on previous studies. Moreover, many catalysts have an issue of insufficient coverage of *CO caused by morphology and/or structure, thus resulting no further coupling to C 3 products. , Therefore, enriching the local concentration of C 1 and C 2 intermediates by altering their diffusion kinetics can provide the possibility of promoting C 3 production. , However, achieving such a target remains a grand challenge, such as the controlled nanoscale adjustment of the same series of catalysts.…”
mentioning
confidence: 99%